2012
DOI: 10.1001/archdermatol.2012.504
|View full text |Cite
|
Sign up to set email alerts
|

Practice Gaps—The Barriers and the Promise of Teledermatology

Abstract: for his valuable insights and guidance regarding the design of this project and Amber Harrison for her administrative support of this project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The developers of the new teledermatology model found that facilitators (organizational infrastructure, training, and support) significantly influence the intention to use teledermatology ( 36 ). Training should include how teledermatology provides access to timely dermatologic care, how physicians should take high-quality images and how to send images securely ( 38 ). Especially the organizational context of the teledermatology implementation is very important ( 36 ), do individuals believe that this organizational infrastructure provides support to use the system?…”
Section: Methodsmentioning
confidence: 99%
“…The developers of the new teledermatology model found that facilitators (organizational infrastructure, training, and support) significantly influence the intention to use teledermatology ( 36 ). Training should include how teledermatology provides access to timely dermatologic care, how physicians should take high-quality images and how to send images securely ( 38 ). Especially the organizational context of the teledermatology implementation is very important ( 36 ), do individuals believe that this organizational infrastructure provides support to use the system?…”
Section: Methodsmentioning
confidence: 99%
“…Teledermatology has been shown to increase patient satisfaction by providing faster access to consultation as opposed to in-person visits for specific populations. While teledermatology presents opportunities for dermatological education with primary care physicians, continued communication and follow up with referring physicians as well as the incorporation of training in dermatology residency programs are significant aspects for future success in the field ( Edison et al, 2012 ). With the rapid advancements in technology, developing a practical and affordable platform for teledermatology could be an essential component for efficient and cost-effective care in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For a subset of patients, teledermatology may serve as a convenient and accepted method of delivering care [23]. Patients seem to be satisfied by the care they receive with teledermatology [14,17], and lack of experience or comfort with the modality does not seem to present a significant concern for diagnosing physicians [24]. Nevertheless, some concerns remain.…”
Section: Discussionmentioning
confidence: 99%